Neuritin Inhibits Notch Signaling through Interacted with Neuralized to Promote the Neurite Growth - Zhang, Pan; Luo, Xing; Guo, Zheng; Xiong, Anying; Dong, Hongchang; Zhang, Qiao; Liu, Chunyan; Zhu, Jingling; Wang, Haiyan; Yu, Na; Zhang, Jinli; Hong, Yu; et al. (Frontiers in Molecular Neuroscience, 2017)
Neuritin plays a key role in neural development and regeneration by promoting neurite outgrowth and synapse maturation. However, the mechanism of neuritin in modulating neurite growth has not been elucidated. Here, using yeast two-hybrid we screened and discovered the interaction of neuritin and neuralized (NEURL1), which is an important regulator that can activate Notch signaling through promoting endocytosis of Notch ligand. And then we identified the interaction of neuritin and neuralized by co-immunoprecipitation (IP) assays, and clarified that neuritin and NEURL1 were co-localized on the cell membrane of SH-SY5Y cells. Moreover, neuritin significantly suppressed Notch ligand Jagged1 (JAG1) endocytosis promoted by NEURL1, and then inhibited the activation of Notch receptor Notch intracellular domain (NICD) and decreased the expression of downstream gene hairy and enhancer of split-1 (HES1). Importantly, the effect of neuritin on inhibiting Notch signaling was rescued by NEURL1, which indicated that neuritin is an upstream and negative regulator of NEURL1 to inhibit Notch signaling through interaction with NEURL1. Notably, recombinant neuritin restored the retraction of neurites caused by activation of Notch, and neurite growth stimulated by neuritin was partially blocked by NEURL1. These findings establish neuritin as an upstream and negative regulator of NEURL1 that inhibits Notch signaling to promote neurite growth. This mechanism connects neuritin with Notch signaling, and provides a valuable foundation for further investigation of neuritin’s role in neurodevelopment and neural plasticity.